Research advances in m6A methylation and sepsis - Zhang, Lifan; Chen, Wenjuan; Liu, Yafeng; Zhang, Shujun; Yin, Bingyou; Liu, Kaijie; Gu, Xinyu; Hu, Xinjun (Frontiers in Cell and Developmental Biology, 2025)
Sepsis is an infection-induced syndrome driven primarily by dysregulated host inflammatory responses. This process induces complex physiological changes that provoke systemic inflammation and multi-organ dysfunction, severely threatening survival in advanced cases. N6-methyladenosine (m6A), the most prevalent eukaryotic RNA modification, orchestrates crucial regulatory functions across biological processes and is a focal point in epigenetics. This modification is dynamically controlled by three protein classes: writers that catalyze m6A deposition, erasers that mediate its removal, and readers that decode modification signals. Substantial evidence implicates m6A dysregulation in sepsis-induced multi-organ damage, encompassing cardiovascular dysfunction, acute lung injury, and acute kidney injury. This review synthesizes current mechanistic insights into m6A’s role in sepsis pathogenesis. By delineating how m6A governs inflammatory cascades and organ injury pathways, we evaluate its therapeutic targeting potential, providing translational frameworks for future research.